Vacuuming in the nude : and other ways to get attention - Rowe, Peggy; Rowe, Mike, 1962- ([Place of publication not identified] : Forefront Books, 2022)
"Peggy Rowe is at it again--this time giving a hilarious inside look at her writing career."--Provided by publisher.
Rowe has been writing all of her adult life- even through years of constant rejection from publishing houses. Between her tenacity and the encouragement of her family, her breakthrough finally came-- at the age of eighty! Here she shares her journey of attending myriad writers' conferences and honing her ability to see humor in everyday situations. Along the way Rowe delivers a hilarious array of stories that reflect her addiction to making people laugh. Even in her cancer support group, she manages to use her humor to affect others for the good. -- adapted from jacket
Foreword -- Getting it write -- Playing the game -- Here I come! -- Slush pile 101 -- And write, I did! -- At last! -- A new frontier -- In my head -- Making a difference -- The shorter and the plainer, the better -- A critic indeed -- Family ties - Madame Secretary -- The book in the drawer - You've got to be kidding! -- A memoir, she wrote.
110765
Keywords: Rowe, Peggy; Women authors, American -- 21st century -- Biography; Authors, American -- 21st century -- Biography; American wit and humor -- Women authors; Autobiographies